(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article presents the average data of three-year production tests of Jerusalem artichoke varieties previously zoned by us for economic efficiency in the Chui Valley of Kyrgyzstan. The Blank variety has the highest profit (1341900 soms per 1 ha), with a profitability level of 552.9%, followed by the Leningrad variety with a profitability of 381.9%. The French purple variety has relatively low values – 307.1%. The other three varieties – Salad, Nakhodka and Interest have approximately the same profitability levels: 344.3-248.4%. It turned out that the cultivation of Jerusalem artichoke as a raw material for the food, pharmaceutical industry and as feed for farm animals and birds is economically more profitable compared to other agricultural plants.